Table of contents - Boothman, Derek (International Gramsci Journal, 2023)
This is the Abstract of the cover page of the International Gramsci Journal Vol. 5(1). It is the mural by the artist Massimo Spiga in the square designed by the architect Simone Coni in Gramsci’s birthplace (Ales), Sardinia, and illustrates the story, based on a childhood experience, which Gramsci wrote in a letter to his son Delio (22 February 1932).